Detection of Epicatechin in Camellia sinensis Leaves by Thin Layer Chromatography and High Performance Liquid Chromatography Techniques - ibrahim, Ruaa mohammed; Zahraa Suhail Nassir (Iraqi Journal of Pharmaceutical Sciences, 2022)
The current study performed in order to detect and quantify epicatechin in two tea samples of Camellia sinensis (black and green tea) by thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). Extraction of epicatechin from black and green tea was done by using two different methods: maceration (cold extraction method) and decoction (hot extraction method) involved using three different solvents which are  absolute ethanol, 50% aqueous ethanol and water  for both extraction methods using room temperature and direct heat respectively. Crude extracts of two tea samples that obtained from two methods were fractionated by using two solvents with different polarity (chloroform and ethyl acetate). Qualitative and quantitative determinations of epicatechin in tea samples were investigated. Epicatechin identification was made by utilizing preliminary chemical tests and TLC. This identification was also boosted by HPLC and the quantity of epicatechin was determined in all ethyl acetate fractions of two tea samples. This research revealed the existence of epicatechin in black and green tea according to TLC and HPLC. Aqueous ethanol 50% was the best solvent for extraction of epicatechin from leaves of tea. Quantitative estimation of epicatechin by HPLC revealed that ethyl acetate fraction of DGTAE contains the higher concentration of epicatechin than other analyzed fractions. Conclusion, tea is an excellent source of catechins particularly epicatechin that possessed various pharmacological effects.